Analisis Biaya dan Luaran Klinik Terapi Remdesivir dibandingkan Favipiravir pada COVID-19 Derajat Sedang: Perspektif Provider - Aniq, Laduna; Andayani, Tri Murti; Endarti, Dwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
The COVID-19 pandemic cases affect health and the economy and have become a burden for the global community. Effective and specific antiviral for COVID-19 is still controversial and has yet to be found. Antiviral use is the main mitigation strategy that tends to be more cost-effective but varies in effectiveness and cost depending on various factors. This study aims to evaluate the effectiveness, safety, and cost of antiviral therapy in moderate COVID-19. This observational-analytic study used a retrospective cohort design. Subjects were hospitalized patients with moderate COVID-19 who received antivirals in July-October 2021 and January-March 2022. Therapy effectiveness was measured by lowered NLR (Neutrophil-to-Lymphocyte Ratio) to a normal level and length of stay (LOS). Drug safety includes adverse drug events. The cost of therapy was calculated based on the hospital’s perspective (provider), using direct medical costs. A total of 170 patients were divided into two groups (94 patients remdesivir and 76 patients favipiravir). In this arm, there were 45 patients with lowered NLR (21 patients reached the target and 24 patients did not). The effectiveness of favipiravir and remdesivir was 70.6% and 32.1%. Remdesivir may lower NLR (2.92) versus favipiravir (1.55). Favipiravir had a shorter LOS than remdesivir (8 vs 9 days). Adverse drug events observed in remdesivir were nausea (47.9%) and abdominal pain (22.3%), while in favipiravir nausea (53.9%) and vomiting (22.4%). The average total cost of remdesivir is higher than favipiravir (IDR 19,772,985 vs IDR 13,819,727). Favipiravir has higher efficacy and a shorter LOS with a lower average total cost than remdesivir.